1991
DOI: 10.1002/app.1991.070420907
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of water by nylon 66 and kevlar 29. Equilibria and kinetics

Abstract: SYNOPSISThe sorption of water by nylon 66 and Kevlar 29 fabrics was studied over a range of 20-98% relative humidities a t 27°C. Equilibrium and rate relationships were developed from the data in this study and from nylon 66 and nylon 6 data of other studies involving fiber and film. The ratio of sorbed moisture to amide concentration is, on average and at high relative humidities, one water molecule per amide unit. The nylon equilibrium data show that there exist threshold relative humidities above and below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
(10 reference statements)
1
13
0
Order By: Relevance
“…When the ambient temperature exceeds approximately 75 C, the rotation of these constrained molecules is initiated, providing a pathway for water molecules to penetrate into noncrystalline regions and may interfere with the hydrogen bonds of molecular chains, resulting in the distortion of the molecular packing. [11][12][13]22 It has been shown also in literature 14 that the water molecules can irreversibly react with amide groups of Kevlar fiber, resulting in clusters of water-amide complex molecules. Chatzi et al 23 reported three different O-H stretching vibrations associated with absorbed water in Kevlar fibers.…”
Section: Resultsmentioning
confidence: 97%
“…When the ambient temperature exceeds approximately 75 C, the rotation of these constrained molecules is initiated, providing a pathway for water molecules to penetrate into noncrystalline regions and may interfere with the hydrogen bonds of molecular chains, resulting in the distortion of the molecular packing. [11][12][13]22 It has been shown also in literature 14 that the water molecules can irreversibly react with amide groups of Kevlar fiber, resulting in clusters of water-amide complex molecules. Chatzi et al 23 reported three different O-H stretching vibrations associated with absorbed water in Kevlar fibers.…”
Section: Resultsmentioning
confidence: 97%
“…It is then of crucial importance to study and understand the role of the amorphous phase on the mechanical properties and how the mechanical properties of PA6,6 are affected by modifying the molecular mobility. In order to obtain PA6,6 samples having different molecular mobility states, two ways were considered herein: modifying PA6,6 by adding additives or co‐monomers; conditioning polyamide samples at different hygrometry levels, since PA6,6 T g decreases significantly in presence of water (plasticization effect) . The yield stress (σ Y ) and Young's modulus ( E ) measured by tensile tests as well as the brittle‐tough transition temperature ( T B/T ) measured by Charpy impact tests are assessed for such PA6,6 samples.…”
Section: Introductionmentioning
confidence: 99%
“…13 A similar investigation in this area was also conducted in our laboratory, and the results showed that the amount of absorbed moisture could be markedly reduced by blending Nylon 6 with t-butyl-novolac. 6 It is generally believed that the amide groups in Nylon 6 are responsible for the moisture uptake.…”
Section: Moisture Absorptionmentioning
confidence: 71%
“…To gain insight to the nature of the specific interaction, 13 C NMR experiments were devised to study the model compounds N-methyl acetamide and p-cresol representing nylon and polymers containing phenol groups, respectively. Various types of possible specific interactions could be proposed in accordance with Scheme 1.…”
Section: Moisture Absorptionmentioning
confidence: 99%